Development of Microbiome Biobanks – Challenges and Opportunities. Issue 2 (February 2021) - Ryan, M.J.; Schloter, M.; Berg, G.; Kostic, T.; Kinkel, L.L.; Eversole, K.; Macklin, J.A.; Schelkle, B.; Kazou, M.; Sarand, I.; Singh, B.K.; Fischer, D.; et al.
Abstract : The microbiome research field is rapidly evolving, but the required biobanking infrastructure is currently fragmented and not prepared for the biobanking of microbiomes. The rapid advancement of technologies requires an urgent assessment of how biobanks can underpin research by preserving microbiome samples and their functional potential.